University teachers’ perceptions about assessment practices: a study in five Portuguese universities - Pereira, Diana (2017)
This paper looks at how Portuguese university teachers look at assessment in Higher Education. It focuses on their perspectives about assessment in higher education after the implementation of the Bologna Process, the connection between assessment, teaching and learning process and the selection of criteria and methods of assessment. Data were collected through face-to-face interviews and online open-ended questionnaires in five Portuguese Public Universities in different fields of knowledge. In total, 57 teachers participated in this study. Findings are presented according the categories emerging from the data. Issues of change in assessment practices, the connection between teaching, learning and assessment as well as difficulties to assessing students’ work are analysed. Implications of the findings are discussed.